Untethered Micro/Nanorobots for Remote Sensing: Toward Intelligent Platform - Wang, Qianqian; Yang, Shihao; Zhang, Li (Nano-Micro Letters, 2023)
Untethered micro/nanorobots that can wirelessly control their motion and deformation state have gained enormous interest in remote sensing applications due to their unique motion characteristics in various media and diverse functionalities. Researchers are developing micro/nanorobots as innovative tools to improve sensing performance and miniaturize sensing systems, enabling in situ detection of substances that traditional sensing methods struggle to achieve. Over the past decade of development, significant research progress has been made in designing sensing strategies based on micro/nanorobots, employing various coordinated control and sensing approaches. This review summarizes the latest developments on micro/nanorobots for remote sensing applications by utilizing the self-generated signals of the robots, robot behavior, microrobotic manipulation, and robot-environment interactions. Providing recent studies and relevant applications in remote sensing, we also discuss the challenges and future perspectives facing micro/nanorobots-based intelligent sensing platforms to achieve sensing in complex environments, translating lab research achievements into widespread real applications. Highlights: 1 A systematic review of latest developments of untethered micro/nanorobots-based remote sensing systems with an emphasis on designing new coordinated control and sensing approaches. 2 The propulsion/motion control, functionalization of micro/nanorobots, sensing mechanisms, and applications are reviewed based on the up-to-date works. 3 The design and application of micro/nanorobot-based sensing platforms are discussed with the goal of building intelligent remote sensing systems.